2019
DOI: 10.7150/thno.34576
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nanomachines as Stimuli-Responsive Gatekeepers on Mesoporous Silica Nanoparticles for Antibiotic and Cancer Drug Delivery

Abstract: Major objectives in nanomedicine and nanotherapy include the ability to trap therapeutic molecules inside of nano-carriers, carry therapeutics to the site of the disease with no leakage, release high local concentrations of drug, release only on demand - either autonomous or external, and kill the cancer cells or an infectious organism. This review will focus on mesoporous silica nanoparticle carriers (MSN) with a large internal pore volume suitable for carrying anticancer and antibiotic drugs, and supramolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 72 publications
0
61
0
Order By: Relevance
“…For instance, Glinert and coworkers tested a protective antigen based vaccine and found that it was effective against subcutaneous spore challenge but the effi cacy was limited for systemic challenges like intravenous application of virulent strains or mutants with defi cient anthrax toxin (65). Therapies of infectious diseases can be further improved by nanoparticles serving like drug carriers, supporting material for antigen presentation during vaccination or material releasing antibiotics for a wider time span (69)(70)(71)(72)(73)(74)(75)(76). Though there are no relevant studies on anthrax, the applicability of nanoparticles in the therapy can be inferred for the future.…”
Section: Anthrax Therapymentioning
confidence: 99%
“…For instance, Glinert and coworkers tested a protective antigen based vaccine and found that it was effective against subcutaneous spore challenge but the effi cacy was limited for systemic challenges like intravenous application of virulent strains or mutants with defi cient anthrax toxin (65). Therapies of infectious diseases can be further improved by nanoparticles serving like drug carriers, supporting material for antigen presentation during vaccination or material releasing antibiotics for a wider time span (69)(70)(71)(72)(73)(74)(75)(76). Though there are no relevant studies on anthrax, the applicability of nanoparticles in the therapy can be inferred for the future.…”
Section: Anthrax Therapymentioning
confidence: 99%
“…Local therapy is rapidly developing as a promising tool for the treatment of several diseases such as tumors and osteomyelitis. 4,13 This approach can promote the availability of high concentrations of drug at the disease site and can reduce side effects. To reduce the reinfection rate of chronic osteomyelitis therapy, the drug delivery material should be biodegradable to eliminate the need to remove the material after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1). [29][30][31] These studies have demonstrated that antimicrobial molecules loaded into such delivery nanoparticles, either through physical encapsulation or chemical conjugation, exhibited an improved pharmacokinetic prole and therapeutic index, as compared to their free drug counterparts. Nevertheless, there are also drawbacks with delivery systems, especially those that are composed of a single material (non-hybrid), such as low drug loading efficiency, premature drug release, and rapid clearance of these nanoparticles mediated by the mononuclear phagocyte system (MPS).…”
Section: Introductionmentioning
confidence: 99%